2016
DOI: 10.1007/s10661-016-5619-2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment of mining industry solid pollution in the mercurial district of Azzaba, northeast Algeria

Abstract: To date, there have been few detailed studies regarding the impact of mining and metallogenic activities on solid fractions in the Azzaba mercurial district (northeast Algeria) despite its importance and global similarity with large Hg mines. To assess the degree, distribution, and sources of pollution, a physical inventory of apparent pollution was developed, and several samples of mining waste, process waste, sediment, and soil were collected on regional and local scales to determine the concentration of Hg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…On the opposite side of our study in northeastern Algeria, studies on the environmental assessment of the mining industry in the Azzaba region proved that there is a large contamination of several minerals, lead and zinc, the most prevalent of which is mercury, reaching 1%. (Seklaoui et al, 2016)The same studies of an abandoned mine area in South Korea indicated that the average concentrations of trace metals in farmland soils for As, Pb, Cd, and Zn were (5,99), (76,2),( 0,88),( 128,3) mg/kg, respectively, which exceeded the national limits. In particular, the total concentration of Pb was found to be more than 250 times the national limit of 200 mg/kg.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…On the opposite side of our study in northeastern Algeria, studies on the environmental assessment of the mining industry in the Azzaba region proved that there is a large contamination of several minerals, lead and zinc, the most prevalent of which is mercury, reaching 1%. (Seklaoui et al, 2016)The same studies of an abandoned mine area in South Korea indicated that the average concentrations of trace metals in farmland soils for As, Pb, Cd, and Zn were (5,99), (76,2),( 0,88),( 128,3) mg/kg, respectively, which exceeded the national limits. In particular, the total concentration of Pb was found to be more than 250 times the national limit of 200 mg/kg.…”
Section: Resultsmentioning
confidence: 93%
“…There are two sources of trace metals, the human source is the mining and fertilizer industries, and the natural source is the crust (Romic & Romic, 2003).To identify sources and understand the spatial variability of heavy metals in soils, their concentrations and spatiotemporal determination are determined. The distribution (Wang et al, 2020) is used to calculate pollution indices and determine their toxicity (Adnan et al, 2022), due to the high toxicity of arsenic (As), cadmium (Cd), lead (Pb) and mercury (Hg) are among the priority minerals available to study pollution (Seklaoui et al, 2016;Xu et al, 2021). The African continent is an important source of mineral resources in the world with 30%, and the largest reserves of minerals such as gold (Darimani et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is considered a more or less developed urban center, 48 inhabited by more than 60,000 inhabitants. The main economic resources of the region of Azzaba are mining and agriculture, 49 knowing that the majority of the region is occupied by agricultural activity. It is characterized by an open society and mixed cultures, but it maintains its customs, such as the use of cafe terraces as an essential place for the daily gathering between groups or an individual relaxation place, where the customer can experience a meeting and play board games.…”
Section: Methodsmentioning
confidence: 99%
“…In a small number of studies on industrial environmental efficiency and pollution problems, scholars often focus on a specific heavy pollution industry, studying the pollution and other problems it causes to the environment. Seklaoui et al (2016) selected the mining industry and conducted a scientific assessment of the environmental pollution caused by it [15]. Hutton and Shafahi (2019) selected the leather industry and studied the waste of water pollution in the leather manufacturing process [16].…”
Section: Literature Reviewmentioning
confidence: 99%